(untitled) (Nexus International Journal of Science and Education, 2024)
This study uncovered the experiences, coping mechanisms used, and educational insights the Junior High School teachers learned in navigating inclusion in the classroom. A qualitative approach to research phenomenological from the Eight (8) Junior High School, Teachers from the different schools in Governor Generoso South District. Experiences in navigating inclusion in the classroom were observed: addressing individual needs, building relationships with students and families, dealing with challenges and barriers, and adapting varied teaching strategies. The coping mechanisms used in addressing the challenges were as follows: collaborating with other teachers, attending professional development, engaging parents and community, and culturally responsive teaching. Finally, the educational insights learned from teachers' experiences: The need for ongoing professional development, the importance of building positive relationships with students and families, the need for collaboration, and the benefits of using student-centered and differentiated instruction. All these themes investigated the effectiveness of different training and professional development programs for Junior high school teachers in enhancing their understanding of inclusive classroom pedagogy, strategies for accommodating diverse learning needs, and creating supportive classroom environments. This study may also be published in any respectable research journal.